A SLC16A1 Mutation in an Infant With Ketoacidosis and Neuroimaging Assessment: Expanding the Clinical Spectrum of MCT1 Deficiency - Al-Khawaga, Sara; AlRayahi, Jehan; Khan, Faiyaz; Saraswathi, Saras; Hasnah, Reem; Haris, Basma; Mohammed, Idris; Abdelalim, Essam M.; Hussain, Khalid (Frontiers in Pediatrics, 2019)
The solute carrier family 16 member 1 (SLC16A1) gene encodes for monocarboxylate transporter 1 (MCT1) that mediates the movement of monocarboxylates, such as lactate and pyruvate across cell membranes. Inactivating recessive homozygous or heterozygous mutations in the SLC16A1 gene were described in patients with recurrent ketoacidosis and hypoglycemia, a potentially lethal condition. In the brain where MCT1 is highly localized around axons and oligodendrocytes, glucose is the most crucial energy substrate while lactate is an alternative substrate. MCT1 mutation or reduced expression leads to neuronal loss due to axonal degeneration in an animal model. Herein, we describe a 28 months old female patient who presented with the first hypoglycemic attack associated with ketoacidosis starting at the age of 3-days old. Whole exome sequencing (WES) performed at six months of age revealed a c.218delG mutation in exon 3 in the SLC16A1 gene. The variant is expected to result in loss of normal MCT1 function. Our patient is amongst the youngest presenting with MCT1 deficiency. A detailed neuroimaging assessment performed at 18 months of age revealed a complex white and gray matter disease, with heterotopia. The threshold of blood glucose to circumvent neurological sequelae cannot be set because it is patient-specific, nevertheless, neurodevelopmental follow up is recommended in this patient. Further functional studies will be required to understand the role of the MCT1 in key tissues such as the central nervous system (CNS), liver, muscle and ketone body metabolism. Our case suggests possible neurological sequelae that could be associated with MCT1 deficiency, an observation that could facilitate the initiation of appropriate neurodevelopmental follow up in such patients.